Descriptive Analysis of Regional Development Indicators by Regency-City in West Nusa Tenggara Province - Yuniati, Musniasih; Baiq Salkiah; Desi Suryati; Yorman (PT FORMOSA CENDEKIA GLOBAL, 2023)
The success of a region's development is measured by several indicators such as HDI, regional inequality, economic growth and poverty levels. The aim of the research is to determine the success of regional development according to city districts in West Nusa Tenggara Province based on regional development indicators. The research method used is a qualitative research method based on quantitative data. The results of the research show that the HDI of districts and cities in West Nusa Tenggara province is in the medium category, namely 50-79. in districts and cities in West Nusa Tenggara Province is fluctuating and tends to increase in 2021